HIV pre-exposure prophylaxis during the SARS-CoV-2 pandemic: Results from a prospective observational study in Germany - M. Uhrmacher; M. Uhrmacher; A. Skaletz-Rorowski; A. Skaletz-Rorowski; S. Nambiar; S. Nambiar; A. J. Schmidt; A. J. Schmidt; P. Ahaus; P. Ahaus; K. Serova; I. Mordhorst; et al. (Frontiers Media S.A., 2022)
AimsSince 2017, HIV pre-exposure prophylaxis (PrEP) care has been provided through an intersectoral collaboration at WIR (Walk-in-Ruhr, Center for Sexual Health and Medicine, Bochum, Germany). The aim of this study was to establish possible impact of COVID-restrictions on the sexual behavior of PrEP users in North Rhine-Westphalia.MethodsThe current PrEP study collected data of individuals using PrEP, their sexual behavior and sexually transmitted infections (STIs) before (each quarter of year 2018) and during the COVID-19 pandemic (each quarter of year 2020).ResultsDuring the first lockdown in Germany from mid-March until May 2020, PrEP-care appointments at WIR were postponed or canceled. Almost a third of PrEP users had discontinued their PrEP intake in the 2nd quarter of 2020 due to alteration of their sexual behavior. The number of sexual partners decreased from a median of 14 partners in the previous 6 months in 1st quarter of 2020, to 7 partners in 4th quarter of 2020. Despite such a significant reduction in partner number during the pandemic in comparison to the pre-pandemic period, a steady rate of STIs was observed among PrEP users in 2020.ConclusionThe SARS-CoV-2-pandemic has impacted PrEP-using MSM in North Rhine-Westphalia with respect to their PrEP intake regimen and sexual behavior in 2020. Our study revealed a steady rate of STI among PrEP users even during the pandemic, thus highlighting the importance of ensuring appropriate HIV/STI prevention services in times of crisis.